2007
DOI: 10.1007/s00415-006-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of motor nueron disease in Scotland

Abstract: Between 1989 and 1998, 1226 cases of ALS/MND were identified in Scotland, with mean age of onset 65.2 (SD 11.9) years for men and 67.2 (SD 11.0) for women. Annual standardized incidence was 2.40 per 100,000 (95% CI 2.22-2.58). Using capture recapture methods we confirm a high level of case ascertainment for each year of study. Incidence and ascertainment of ALS has remained stable in a large population over a prolonged period of time. Large population-based databases can be used to test aetiological hypotheses. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
59
7
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 7 publications
(5 reference statements)
7
59
7
2
Order By: Relevance
“…The percentage of bulbar-onset patients is also most common than the reported in other studies 2,3,11,12,14 . As bulbar-onset ALS may be more common in the oldest age groups, this difference may be explained by the higher proportion of elderly patients in our population.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…The percentage of bulbar-onset patients is also most common than the reported in other studies 2,3,11,12,14 . As bulbar-onset ALS may be more common in the oldest age groups, this difference may be explained by the higher proportion of elderly patients in our population.…”
mentioning
confidence: 59%
“…Only two previous studies have found a proportion of cases of people over 80 years above 10% 2,24 . For example, a recent study in the Limousin region in France found higher incidences in the oldest age groups, where ALS incidence showed a progressive rise with age culminating in a large peak between 65…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Os critérios diagnósticos utilizados permitem classificar a ELA em quatro níveis: suspeita, possível, provável e definitiva 12 . A ELA tem uma incidência mundial em torno de 1,0 a 2,5 casos/100.000 habitantes 13 , aumentando para 7,5 casos/100.000 habitantes na população acima dos 80 anos 14 . Algumas peculiaridades descritas na literatura despertam interesse quanto à alta incidência verificada na ilha de Guam e na Nova Guiné 15,16 .…”
Section: Introductionunclassified